The Effect of ESG Pillar on Dividend Policy with ROA as Intervening Variable: Study in Malaysia Capital Market - Syarifah, Putri Nur; Hersugondo, Hersugondo (Research Horizon, 2024)
This study aims to find the impact of ESG Principles on Dividend Policy in companies in Malaysia. Malaysia was determined to be the object of research because Malaysia is one of the countries with the highest 10-year environmental change in the Southeast Asian region with an index value of 10.30. The results obtained indicate that companies in Malaysia have implemented the ESG Principles although the detected influence is only limited to the governance pillar and environmental pillar. The results also indicate that during the crisis during COVID-19. ROA has a negative impact on DPR because companies still have to maintain their cash flow so dividends cannot be distributed as in previous years. Positive leverage also indicates that companies want to maintain investor confidence by continuing to pay dividends during times of crisis.